KONSEP DIRI PADA MASA DEWASA AWAL YANG MENGALAMI MALADAPTIVE DAYDREAMING - Wijaya, Rafi Bagus Adi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Maladaptive daydreaming (MD) is a condition that shows prolonged daydreaming behavior to forget the time, of course, affecting individuals both in personal and social aspects. In the early adulthood, the individual is charged with a large developmental task and responsibility, therefore the self-concept determines how a person acts in overcoming various situations. This study aims to determine self-concept in early adult individuals who experience MD, including the factors that influence self-concept in early adulthood who experience MD. The research method used is qualitative research with a case study approach. Data collection using techniques observation, interviews, and documentation, on two subjects including 1 male and 1 female. In analyzing the data, researchers perform data reduction, data display, and drawing conclusions, while to test the validity of the data using triangulation. The results of this study indicate that the subject has a negative self-concept due to a lack of attention, support and motivation from the family and is carried away in maladaptive daydreaming, then the impact of the negative self-concept of the subject is that it seems to have difficulty facing reality in fulfilling developmental tasks, such as work, or establishing relationships with other people and difficult to determine the goals of life at his age